Pilot Study: Impact of a Gluten-Free Diet on Symptoms and Severity of Fibromyalgia - Ana Carolina Garcia de las Ballonas Campolina; Cristina Maria Mendes Resende; Paola Caroline Lacerda Leocádio; Rachel Horta Freire; Melissa Tainan Silva; Luana Moreira Fonseca; Karine Silva de Andrade; Luis Rodrigo; Aloisio Joaquim F. Ribeiro; Denise Carmona Cara; Jacqueline Isaura Alvarez-Leite (International Journal of Nutrition, 2020)
Fibromyalgia (FM) is a condition of chronic and widespread pain, with several associated symptoms. Previous studies suggested that gluten could influence the severity and frequency of FM symptoms. This work aimed to assess the impact of a gluten-free diet (GFD) in the symptoms and severity of this disease. Fourteen patients with previous FM diagnosis were kept on a gluten-free diet for eight weeks (Phase 1). After that, they were held on the gluten-free diet and received capsules of isolated rice protein (placebo) for seven days, followed by capsules containing 8.4g/day vital gluten for additional seven days (Phase 2). Questionnaires evaluating the number and severity of FM symptoms, the impact of FM on daily routine as well as inflammatory blood markers were assessed in each phase. Results showed that after eight weeks of GFD, we observed a reduction in the impact of FM on daily routine and number of symptoms and sensitive points. However, a seven days challenge with 8.4g of gluten did not worsen these symptoms or the inflammatory markers compared with the placebo challenge. We concluded that the gluten-free diet was associated with the attenuation of main symptoms and improvement of life quality in FM patients. Nonetheless, gluten challenge had no impact on those parameters, suggesting that gluten is not the major dietary component responsible for these improvements. Further studies are needed to elucidate the relationship between gluten intake and fibromyalgia.
Keywords: Fibromyalgia